Analysis Of The Mechanism Of Removal And Termination Of Village Equipment By The Regency Of Gorontalo Regency - Misbahul Muslimin (Estudiante Law Journal, 2021)
Abstract: In carrying out its autonomy, the village is led by a village head to run the government in the village and provide services to the community. In carrying out its obligations, duties, and functions, the village head is assisted by village officials which include the village secretary, regional executive, and technical implementer. The dismissal of Village Officials that occurred in Gorontalo Regency was one of the inappropriate policy decisions by the Regent of Gorontalo Regency where in the event the dismissed Village Apparatus did not meet the requirements for the dismissal. The type of research used is empirical legal research. Empirical research is a type of research that uses empirical facts taken from human behavior, both verbal behavior obtained through interviews and real behavior made from direct observation. Dismissal of Village Apparatus carried out by the Regent of Gorontalo Regency violates existing rules, where the dismissal of Village Apparatus is the authority of the Village Head in consultation with the Camat. This problem occurs because of a lack of understanding of the rules for the appointment and dismissal of Village Apparatus and also the incompatibility of the rules governing village government and the rules governing Village Apparatus.